COST-UTILITY ANALYSIS OF FENOFIBRATE IN SLOWING PROGRESSION OF DIABETIC RETINOPATHY IN VIETNAM (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the cost-utility of Fenofibrate in slowing the progression of diabetic retinopathy in Vietnam.Subjects and methods: A model-based cost-utility analysis was performed from the payer perspective and the societal perspective, over a 10-year time horizon. A Markov model with 9 health states was used with a 1-year cycle length. The parameters of cost, clinical efficacy, and quality of life were collected from published literature.Results: Fenofibrate was associated with both higher costs and greater clinical benefits. Compared to standard of care, Fenofibrate yielded an additional 0.3 quality-adjusted life years (QALYs). The incremental costs were VND 25.7 million from the societal perspective and VND 34.7 million from the payer perspective. The resulting ICERs per QALY gained were VND 84.5 million and VND 114.1 million, respectively, both falling below the one GDP per capita threshold for Vietnam in 2025. Sensitivity analyses robust the base-case results.Conclusion: Fenofibrate is cost-effective in slowing the progression of diabetic retinopathy in Vietnam.
Keywords: Diabetic retinopathy, Fenofibrate, cost effectiveness, cost utility analysis